A NEW EU ENERGY POLICY: TOWARDS LOCAL DEMOCRACY - Szyrski, Mariusz (Zeszyty Prawnicze, 2018)
This article is one of the last parts of a scientific project conducted in Poland and entitled “The production and use of energy from renewable sources in the municipality as a sphere of municipal management: legal and administrative analysis,” The purpose of this article is to formulate conclusions, mainly in the legal and social aspects, on the production of energy from renewable sources at the local level. One of the main points I address is the definition of “local energy”. The article analyzes the changes in the law on energy, with particular emphasis on the law on renewable energy sources. Te first part presents a historical approach: the most important EU legislation constituting the foundation for the development of European energy. Next I discuss the basic principles of the Winter Package, a set of documents intended to transform the EU’s energy policy. In the final part of the article I attempt to indicate the latest trends in “local energy,” and to give a definition of this phenomenon.